Drug Delivery System In Opthalmic Preparations: Literature Review Article - Nia Yuniarshi (Journal of Applied Psychology and Health Studies, 2025)
Drug delivery system or drug delivery system is a term that explains how a drug can reach a target area to achieve its effect. The preparation given in liquid form then enters the gel phase due to certain triggers such as pH, temperature and the presence of ions. The method used in this research is a literature review article (LRA). Literature search using electronic data sources published between 2013 and 2023 via Google Scholar. In the results of the literature search, 20 pieces of literature were found that met the content criteria. Based on several studies published in the literature, it shows that the drug delivery system aims to release the active substance into the circulatory system until it reaches the receptor, so that the drug provides maximum effect